2019
DOI: 10.1002/slct.201802624
|View full text |Cite
|
Sign up to set email alerts
|

Paper‐Based Disposable Zinc‐Vanadium Fuel Cell for Micropower Applications

Abstract: The emergence properties of paper as the ionic conductor has driven the new development in energy generators mainly micro‐nano scale energy. Instead of the flow channels in conventional fuel cells, the capillary action of the paper controls the flow of the electrolytes. Paper based biofuel cells and electrochemical fuel cells are recent trends in micro‐nano power generation to support the biosensors. In this study, zinc fuel and VO2+4pt oxidant were used to form a membraneless fuel cell. Instead of membrane, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…Most of the PμFCs fed by biomass-derived alcohols reported here are also higher than those reported in the literature, even considering other fuels and oxidants. 16 Under our knowledge, the systems that deliver higher power density than reported here are fed by other liquids, such as formic acid, 17 potassium formate in stacks, 18 zinc and vanadium, 34 and others detailed by Tanveer et al 16 Moreover, the PμFC reported here may benefit further from an improved design, such as folding, 35 adding patterns to change the flow mechanism, 23 changing the size of electrodes, and flow configuration. 16 Figure 6 reveals the limits in terms of the peak power density of the biomass-fed PμFC with different concentrations of alcohols.…”
Section: Fuel Cell Experimentsmentioning
confidence: 68%
“…Most of the PμFCs fed by biomass-derived alcohols reported here are also higher than those reported in the literature, even considering other fuels and oxidants. 16 Under our knowledge, the systems that deliver higher power density than reported here are fed by other liquids, such as formic acid, 17 potassium formate in stacks, 18 zinc and vanadium, 34 and others detailed by Tanveer et al 16 Moreover, the PμFC reported here may benefit further from an improved design, such as folding, 35 adding patterns to change the flow mechanism, 23 changing the size of electrodes, and flow configuration. 16 Figure 6 reveals the limits in terms of the peak power density of the biomass-fed PμFC with different concentrations of alcohols.…”
Section: Fuel Cell Experimentsmentioning
confidence: 68%
“…[ 115 ] Combining with biocompatible materials as assembling unit, such membraneless RFBs can be applied as micro‐nano power supply for biosensors. [ 116 ]…”
Section: Challenges At Anode and Cathode Sidesmentioning
confidence: 99%
“…The most significant advantage of this cell was its lower cost and higher power. Owing to the capillary activity of paper, no pump is needed in this MFEFC 45 …”
Section: Advances In Recent Yearsmentioning
confidence: 99%
“…Owing to the capillary activity of paper, no pump is needed in this MFEFC. 45 For the first time, a MFEFC powered by ethanol-dichromate was invented by Subrata Chandra et al The cell utilized poly-base gel as an electrolyte and molybdenum oxide nanorod catalysts (Fig. 4).…”
Section: Special Fuels Used To Generate Electricity In Mfefcsmentioning
confidence: 99%